2007
DOI: 10.1016/j.jbiotec.2007.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of the plasma membrane ROS-generating NADPH oxidase in CD34+ progenitor cells preservation by hypoxia

Abstract: Hypoxia favored the preservation of progenitor characteristics of hematopoietic stem and progenitor cells (HSPCs) in bone marrow. This work aimed at studying the role of reactive oxygen species (ROS)-generating NADPH oxidase system regulated by hypoxia in ex vivo cultures of cord blood CD34 + cells. The results showed that NADPH oxidase activity and ROS generation were reduced in hypoxia with respect to normal oxygen tension. Meanwhile the ROS generation was found to be inhibited by diphenyleneiodonium (the NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…9 We previously reported that Nox2-derived ROS play an important role in VEGF signaling linked to EC migration and proliferation, as well as reparative angiogenesis in response to hindlimb ischemia in vivo. 11,12 Increasing evidence suggests that ROS are generated by NADPH oxidase in EPCs and stem/progenitor cells, [13][14][15] which are involved in differentiation, proliferation, senescence, or apoptosis depending on cell types and amount of ROS. However, the role of Nox2-based NADPH oxidase in BM and EPCs/progenitor cell function linked to postnatal vasculogenesis remains unknown.…”
mentioning
confidence: 99%
“…9 We previously reported that Nox2-derived ROS play an important role in VEGF signaling linked to EC migration and proliferation, as well as reparative angiogenesis in response to hindlimb ischemia in vivo. 11,12 Increasing evidence suggests that ROS are generated by NADPH oxidase in EPCs and stem/progenitor cells, [13][14][15] which are involved in differentiation, proliferation, senescence, or apoptosis depending on cell types and amount of ROS. However, the role of Nox2-based NADPH oxidase in BM and EPCs/progenitor cell function linked to postnatal vasculogenesis remains unknown.…”
mentioning
confidence: 99%
“…DCFH 2 has also been used as a general indicator of the redox status of HSCs and HPCs (Abbas et al, 2010;Chen et al, 2008a;Chuikov et al, 2010;Fan et al, 2007;Hosokawa et al, 2007;Jang and Sharkis, 2007;Jung et al, 2013;Juntilla et al, 2010;Liu et al, 2009;Pazhanisamy et al, 2011;Piccoli et al, 2007a;Shao et al, 2014;Yahata et al, 2011) (Table 1) (Folkes et al, 2009). Second, the efficiency of oxidation of the intermediate DCFH 2 probe radical into the final product depends on the environmental oxygen concentration (Wrona and Wardman, 2006).…”
Section: Non-specific Detection Of Ros and Rns: Dcfhmentioning
confidence: 99%
“…Second, the efficiency of oxidation of the intermediate DCFH 2 probe radical into the final product depends on the environmental oxygen concentration (Wrona and Wardman, 2006). This issue is of particular importance when DCFH 2 is used as a probe to study the effect of the O 2 concentration on ROS generation in HSCs and HPCs (Fan et al, 2007;Hao et al, 2011). Third, cellular conditions may also alter the oxidation efficiency of DCFH 2 .…”
Section: Non-specific Detection Of Ros and Rns: Dcfhmentioning
confidence: 99%
“…15 In particular, the coexistence in EPCs of different types of ROS generators with different modalities of activation may result in a sophisticated mechanism of redox signaling that can control the balance among cell growth, proliferation and differentiation. 17,18 The NADP + -Noxs, multisubunit membrane-associated enzymes that catalyze the one-electron reduction of oxygen using NADH or NADPH as the electron donor represent an important source of ROS for EPCs. 18,19 The Noxs, including the isoform containing the gp91phox or Nox2 isoform, are sensitively modulated by a wide range of factors, 20,21 including angiotensin-II (AngII), 21 the main effector of the renin-Ang system, which modulates vascular functions and arterial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The NADP + -Noxs, multisubunit membrane-associated enzymes that catalyze the one-electron reduction of oxygen using NADH or NADPH as the electron donor represent an important source of ROS for EPCs. 18,19 The Noxs, including the isoform containing the gp91phox or Nox2 isoform, are sensitively modulated by a wide range of factors, 20,21 including angiotensin-II (AngII), 21 the main effector of the renin-Ang system, which modulates vascular functions and arterial pressure. AngII seems to accelerate the onset of senescence in EPCs isolated from healthy individuals via stimulation of gp91phox expression and ROS production.…”
Section: Introductionmentioning
confidence: 99%